Formulation Development of Losartan Potassium Immediate Release Tablets and Process Optimization using SeDeM Expert System - Imran Tadwee, Sadhana Shahi (Journal of Applied Pharmaceutical Science, 2018)
The present research work aims to develop drug product using SeDeM technique, this technique employed in preformulation studies which reveals direct compression suitability of active pharmaceutical ingredient (API) and excipient in formulation, study also aims to mask the poor flow property of drug substance using SeDeM expert system and prepare robust composition for direct compression. 12 test of SeDeM technique was applied on Losartan potassium and other commonly used excipients, obtained radius values were considered to check suitability and deficiencies of excipients and drug, % corrective excipient is identified and incorporated in formula, F1 to F3 composition derived based on SeDeM outcome, Set of SeDeM test were performed on all 3 blends, optimized composition derived based on IPP value, Tablets compressed using direct compression method, and comparative evaluation done using marketed product. RP value for Losartan potassium found 3.44 which shows poor flow property. Microcrystalline cellulose, Lactose SD, and maize starch RE value estimated 5.66, 7.41, and 5.49 respectively. Lubricated blend of composition F2 found average radius value IPP is 6.68, compressed tablet shown good physical properties, while f1 and f2 values found to be 6 and 68 respectively. Formulation found pharmaceutical equivalent with marketed product and stable as well. Hence SeDeM system can be employed as cost effective, quicker technique for prediction of material behavior in terms of flow.
Keywords: Poor Flow, SeDeM Method,Preformulation, Direct compression,Losartan.